Incentives for dishonesty: An experimental study with internal auditors - Loukas Balafoutas; Simon Czermak; Marc Eulerich; Helena Fornwagner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
This study examines experimentally how dishonest behavior in the form of misreporting others' performance depends on the nature of provided incentives. We conduct a 'lab in the field' experiment with internal auditors during two large conferences in Germany and evaluate their performance and objectivity, measured as the extent to which they truthfully report the performance of other participants in a real-effort task. It has been suggested in the literature that incentive-pay compensation for auditors has the potential to lead to dishonest behavior on their part, for instance when their payoff depends on the performance of the unit that they are auditing. We vary incentives in the experiment from individual (piece rate) to competitive (tournament against another auditor) and collective (based on performance within a team). In line with our hypotheses, we find that incentive-based compensation increases dishonest behavior among internal auditors: competitive incentives lead to under-reporting of other participants' performance, while collective incentives lead to over-reporting of performance.
Keywords: C93; M42; M52; 330; dishonesty; incentives; sabotage; internal audit; experiment